Costs of Overly Broad Recalls - Nyssa Ackerley; Ayesha Berlind; Michael Black; Kevin Kho; Cristina McLaughlin; Aliya Sassi; Aylin Sertkaya; Sheri Walker (Journal of Food Protection)
Overly broad recalls following an FDA advisory occur when the source of an outbreak is originally misidentified or cannot be promptly identified. In this situation, an entire product category might be recalled (e.g., romaine lettuce), such that the recall extends to uncontaminated product lots, imposing spillover costs on entities that would otherwise be unaffected. There are, however, very few published studies that estimate the potential magnitude of these spillover costs. Using a formal structured elicitation methodology, this study develops expert estimates of the spillover costs firms typically incur in responding to an overly broad recall following an FDA product advisory. We find that the range of costs varies widely by type and size of firm, with producers incurring median costs per recall ranging from $3.0 million to $72.7 million per firm, shippers/distributors from $0.1 million to $2.3 million per firm, restaurants from $0.04 million to $1.1 million per firm, and nonrestaurant retailers from $0.1 million to $3.1 million per firm. The results of this study can help inform food policy discussions geared toward assessing the benefits of traceability in terms of avoided costs of overly broad food recalls. Industry is often reluctant to provide estimates on the costs of recalls. This study fills that void by estimating the per-firm costs incurred by food supply chain entities due to overly broad recalls.